The role of irrigated fodder production to supplement the diet of fattening sheep by smallholders in southern Ethiopia - Bezabih, Melkamu; Duncan, Alan J.; Mekonnen, Kindu; Adie, Aberra; Khan, A.K.; Thorne, Peter J. (2016)
Feed shortage and poor quality of available feeds are major constraints for livestock production in the highlands of Ethiopia. A trial was conducted to assess if producing irrigated oat-vetch fodder during the dry period could adequately supplement the diet of fattening sheep and generate additional income for smallholders. A total of 14 farmers and 70 sheep (5 per farmer) were involved in the trial. The farmers supplemented their fattening sheep with 200 g of irrigated oat-vetch fodder per day for about 70 days. The mean daily body weight gain of the fattened sheep ranged from 52 to 110 grams. The partial budget analysis revealed that while farmers with good feeding management could earn an additional income in the range of ETB 55 – 161 per sheep, farmers with the lower rate of weight gain could lose up to ETB 58 per sheep unless purchase and sale prices remained constant. Sheep prices do, however, fluctuate, peaking during major holiday periods occurring during the dry season. Therefore, timing of the fattening period is essential to profitability, and supplemental irrigated fodder production offers smallholders opportunities to produce good quality feed and target favourable markets for fattened animals.